Green Horizons: Enhancing Customer Satisfaction through Quality Experiences, Mediated by Green Perceived Value and Green City Image in Kota Lebong Tourism, Bengkulu Province - Gandasari, Arum Laila; Daulay , Muhammad Yasser Iqbal (Journal of Entrepreneurship and Business, 2024)
Pupose: The objective of this research is to comprehensively analyze the relationship between experience quality and customer green satisfaction, as well as to investigate the mediating roles of green city image and green perceived value in the context of environmentally friendly tourist destinations. Method:This study employs a quantitative-explanatory approach with the population of focus being all visitors to tourist attractions in Lebong City, Bengkulu Province. The exact size of this population cannot be determined. The total sample size for this study is 360 respondents. And analysed using SEM-PLS. Result: The result of this study reveals experience quality influence green satisfaction, green city image, and green perceived value. Also, both green city image and green perceived value mediated the relationship between experience quality on green satisfaction.